Effects of yeast culture addition (Saccharomyces cerevisiae) to Anatolian water buffalo diets on milk composition and somatic cell count - T. Degirmencioglu; T. Ozcan; S. Ozbilgin; S. Senturklu (Mljekarstvo)
This study was carried out to determine the effect of Saccharomyces cerevisiae (SC) addition to dry matter intake, milk yield, milk composition and somatic cell count in Anatolian water buffalo diets (AWB). The SC-treated groups (n = 5 buffalo cow/group) received 30.0 g of SC per buffalo cow per day. Compared to the control group, the SC-treated group consumed more total dry matter (P<0.05; 14.27 vs. 13.50 kg/day) and produced more milk/day (P<0.01; 7.13 vs. 6.22 kg/day). Dietary yeast inclusion significantly increased alfalfa dry matter intake during a 28-day lactation period (P<0.01; 10.41 vs. 9.81 kg/day) compared with the control diet. Yeast application significantly reduced the somatic cell count (SCC) in milk (P<0.05; 3.33 and 1.08 SCC (log 10/mL) for control and SC-treated groups, respectively). The fat (58.40 and 59.00 g/kg), non-fat solids (120.00 and 122.80 g/kg), protein (46.40 and 46.26. g/kg) and lactose components of milk (37.72 and 38.90 g/kg) were similar for both groups. The response of the AWB to supplemental yeast addition improved forage intake and daily milk production but did not affect milk composition. In conclusion; it has been thought that farmers with AWB can benefit from the use of yeast cultures in early lactation diets.